Control of Rhizoctonia solani with extracts from Ovidia andina - Mansilla, Javier Tito; Tarcaya, Verónica P; Cufre , Ingrid M.; Fabrizio, María C.; Wright, Eduardo R.; Broussalis, Adriana M.; Rivera, Marta C. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
New alternatives are needed to control ubiquitous soilborne fungi like Rhizoctonia solani. This work evaluates the activity of extracts from Ovidia andina on this pathogen. Powdered dried leaves and stems were extracted by maceration with dichloromethane (CH2Cl2), methanol and ethanol. An aqueous extract was obtained by decoction, and the hydrodistillation residual water was the aqueous phase after essences production. A strain of R. solani was cultivated on potato dextrose agar supplemented with the extracts, at 1:100 and 1:1000 v/v. The CH2Cl2 extract at 1:100 reduced colony growth (p< 0.0001) and changed hyphal morphology. Five fractions were obtained from the CH2Cl2 extract in a glass column, and TLC analysis showed the presence of coumarins and flavonoids. The CH2Cl2 extract and fractions were diluted in CH2Cl2 or acetone. The efficiency to reduce pathogen growth of fractions 2f and 5f diluted in CH2Cl2 at 1:100 did not differ from the whole extract (p<0.0001). For an in vivo test, beetroot seed balls were incubated in soil infested with R. solani and treated by immersion in the CH2Cl2 extract at 1:100 for different periods of time. As a result, pathogen colonization was diminished by immersion for 120 s and seed germination was normal (p< 0.0001). Additionally, infested soil was treated with the CH2Cl2 extract, and inoculum concentration estimated using beetroot seed balls as baits diminished (p< 0.0001). These results lead us to conclude that O. andina is a source of antifungal components for crop protection against R. solani.